Validation of an axial flow blood pump : computational fluid dynamics results using particle image velocimetry - Su, Boyang (2013)
A magnetically suspended axial flow blood pump is studied experimentally in this article. The pump casing enclosed a three-blade straightener, a two-blade impeller shrouded by a permanent magnet-embedded cylinder, and a three-blade diffuser. The internal flow fields were simulated earlier using computational fluid dynamics (CFD), and the pump characteristic curves were determined. The simulation results showed that the internal flow field was basically streamlined, except the diffuser region. Particle image velocimetry (PIV) measurement of the 1:1 pump model was conducted to validate the CFD result. In order to ensure the optical access, an acrylic prototype was fabricated with the impeller driven by a servomotor instead, as the magnet is opaque. In addition to the transparent model, the blood analog fluid with the refractive index close to that of acrylic was used to avoid refraction. According to the CFD results, the axial flow blood pump could generate adequate pressure head at the rotating speed of 9500 rpm and flow rate of 5 L/min, and the same flow condition was applied during the PIV measurement. Through the comparisons, it was found that the experimental results were close to those obtained by CFD and had thus validated the CFD model, which could complement the limitation of the measurement in assessing the more detailed flow fields of the axial flow pump.